Modul Persiapan Peran Menjadi Ibu terhadap Pengetahuan dan Keterampilan Volunteer Sayang Ibu - Maya Latifatul Masrurroh; Krisdiana Wijayanti; Lanny Sunarjo; Sri Sumarni; Yessy Arisman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effectiveness of the motherhood preparation module. This research method uses Research and Development (R&D) and Quasy Experimental Pretest and Posttest Design. The results showed that the level of knowledge of